The Early Field Systems of the Stonehenge Landscape. (3rd July 2017) - Roberts, David; Last, Jonathan; Linford, Neil; Bedford, Jon; Bishop, Barry; Dobie, Judith; Dunbar, Elaine; Forward, Alice; Linford, Paul; Marshall, Peter; Mays, Simon; Payne, Andy; et al.
ABSTRACT: Recent survey, excavation and analysis in the Stonehenge World Heritage Site (WHS) during 2015 and 2016 has revealed new details of landscape structuration and the deposition of the dead during the Middle Bronze Age. The research reported here demonstrates the existence of early fields or enclosures in the eastern part of the WHS, that was previously thought to be an area of little agricultural or domestic activity in the Bronze Age. These features were succeeded by a major ditch system in which two individuals were buried, an unusual way of dealing with the dead in the Middle Bronze Age. At the same time, the body of a perinatal infant was deposited in a palisade ditch in the western part of the WHS. The paper explores how these actions help elucidate a period of significant change in the landscape around Stonehenge, during which natural features, ancestral monuments and the recent dead were enmeshed in complex ways of bounding and dividing the landscape.